Conducting a Focus Group Discussion in Qualitative Research - Bachtiar, Nia Kurniati; Fariz, Muhammad; Arif, Mohammad Sholikhan (Innovation, Technology, and Entrepreneurship Journal, 2024)
This article aims to explain the focus group discussion, or focus group interview, method in qualitative research. This method is commonly used in many fields, such as organizational studies, health and medicine, and politics. Particularly, this paper elaborates on the characteristics of focus group discussions, outlines their stages, and shares tips and tricks for conducting them. The journal article serves as a comprehensive resource for researchers looking to integrate focus group discussions into their methodology. It offers practical advice on the preparation, execution, and analysis stages of FGDs, thereby enhancing data quality and overall research effectiveness.